LEGAL REVIEW OF FIDUCIARY CONTRACT IMPLEMENTATION OF MOVING GOOD FROM SHARIA ECONOMIC PERSPECTIVE - Eldam Surohman; Rochmad Adi Yulianto; Fauziah Fauziah (Jurnal Hukum Jurisdictie, 2022)
Based on the DSN-MUI fatwa Number 04/DSN-MUI/IV/2000 concerning murabaha, which allows sharia financing institutions to request guarantees from customers with mutual trust to complete obligations and obtain rights arising from the agreement. If the debtor is unable to carry out his obligations or commits a breach of contract (default), then the guarantee execution process can be carried out by the creditor. The execution process of course refers to the provisions of Law Number 42 of 1999 concerning Fiduciary Guarantees in conjunction with the Constitutional Court Decision Number 18/PUU-XVII/2019. In the case study of the Tasikmalaya Religious Court Decision Number 1038/Pdt.G/2020/PA.Tmk regarding the execution of a fiduciary guarantee with a murabahah financing agreement, where the debtor gets financing to obtain 2 units of four-wheeled vehicles but the debtor defaults to the creditor. The legal efforts taken by the creditor against the debtor, namely, through subpoena and mediation, then proceed with submitting an application for the execution of fiduciary guarantees to the religious court in terms of carrying out executions of the collateral guaranteed by the debtor. Therefore, it will be discussed further regarding the decision of the Religious Court by examining the elements contained in the legislation based on the case in the Tasikmalaya Religious Court Decision Study Number 1038/Pdt.G/2020/PA.Tmk.